Trabalho e educação: um estudo sobre os sentidos que os professores se atribuem como trabalhadores na rede particular de ensino de Santa Maria/RS - Michel, Marcelo Dorneles (2014)
This research integrates the study of work, education and public policy, the fundamental components for understanding and possibility of transformation of concrete situations experienced by teachers, in this case, in a specific environment, which is a private school. It is justify the importance of this research since, on labor relations established by the Private Education Network, even as a playing field for various education professionals, have happened and neither significant recurring studies. Therefore, the need to understand the dynamics of labor relations of teachers, senses that this profession is attributed as education workers. The main objective of this study was therefore to investigate the meanings established by the teachers of private schools and educational workers, with the specific aim of understanding labor relations in this particular environment. The theoretical and methodological basis that structured this research was the dialectical analysis, involving the dialectical method and dialectical thinking. By consider this investigation expresses the intention of being a social survey, it was took into account that this type of research has been strongly marked by studies that value the use of quantitative and qualitative methods to describe and explain the phenomena analyzed. This work is guided by the methodology of content analysis as a method adopted to deal with the data collected in the survey. As a procedure it was chosen to conduct a study with a group of ten teachers from six schools. Interviews were conducted with these stakeholders, and the data were analyzed based on content analysis in Bardin (2011), permeated by the perspective of dialectical analysis.